PRINSIP-PRINSIP EKONOMI SYARIâAH PADA SEWALAYAN RAHMAT SYARIâAH DI KOTA PADANGSIDIMPUAN - Siregar, Rosnani (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
Islamic business direct economic or business world full of economic values and ethics, in other words that Islam never separate the economics with ethics. The supermarket or grocery store is a store that sells all kinds of daily necessities. The word is literally taken from the United Kingdom, this means it is a huge market. Goods sold in the supermarket are usually the stuff of daily goods. Sewalayan Grace Shariah as a buying and selling community has showed the appropriate business pattern of Sharia. This is evidenced from the pricing of goods, pricing of honesty in terms of capital and the sales price and the price of conformity with the quality of the goods, and the granting to the purchaser of khiyar khiar khiyar assemblies, aib, khiyar ruyah and khiyar ain. Kesyariahan sewalayan is also visible from the pemasaranya form. The employees look with their nakedness so Moslem clothing protected in accordance with the guidance of Allah and his apostle. Buyers feel comfortable with their appearance with clothing muslimatnya. In addition it also reprimanded employees buyers with courteous and sapa said kindly. Employee memperikan fast assistance to buyers both in terms of the provision of the required goods or pasilitas goods to ease the akutan buyers bring their goods. Employee payroll also conform to Shariah